Successful surgical excision of cerebral abscess caused by Fonsecaea monophora in an immunocompetent patient and review of literature - Dobias, Radim; Filip, Michal; Vragova, Katerina; Dolinska, Dagmar; Zavodna, Petra; Dujka, Ales; Linzer, Petr; Jurek, Patrik; Studena, Barbora; Cerna, Eva; Mrazek, Jakub; Jaworska, Pavla; et al. (Folia microbiologica, 2019)
Cerebral abscesses caused by dark-pigmented Fonsecaea fungi are rare, especially in otherwise healthy individuals. In this case report, we present a 61-year-old man from Moldova, living in the Czech Republic, who had worked as a locksmith on oil platforms in Turkmenistan, Kazakhstan, Sudan, and Iraq since 1999, and was admitted to a neurology ward for a sudden motion disorder of the right leg, dysarthria, and hypomimia. Imaging revealed presence of expansive focus around the left lateral ventricle of the brain and a pronounced peripheral edema. The intracranial infectious focus was excised under intraoperative SonoWand guidance. Tissue samples were histologically positive for dark-pigmented hyphae, suggesting dematiaceous fungi. Therefore, liposomal amphotericin B therapy was initiated immediately. Fonsecaea monophora was provisionally identified using ITS rDNA region sequencing directly from brain tissue. The identification was subsequently confirmed by cultivation and DNA sequencing from culture. The strain exhibited in vitro sensitive to voriconazole (MIC = 0.016 μg/mL) and resistance to amphotericin B (MIC = 4 μg/mL); therefore, the amphotericin B was replaced with voriconazole. Postoperatively, a significant clinical improvement was observed and no additional surgery was required. Based on the literature review, this is the third documented case of cerebral infection due to this pathogen in patients without underlying conditions and the first such case in Europe.
Keywords: Amphotericin B; Ascomycota; Antifungal Agents; ribozomální DNA; DNA, Ribosomal; výsledek terapie; amfotericin B; absces mozku; lidé; Mycoses; Treatment Outcome; mykózy; Male; Czech Republic; imunokompetence; Česká republika; lidé středního věku; mužské pohlaví; Brain Abscess; antifungální látky; Immunocompetence; Middle Aged; Humans